Study on Unexpected Bioenergetic Function of Neuromelanin. Implications in the Biology of Learning and Memory - Herrera, Arturo Solis; Arias, Ruth I. Solis (Recent Research Advances in Biology Vol. 7, 2021)
Progressive Recent Memory loss is the main complaint in Alzheimer’s disease patients. There is not a simple or congruous explanation yet due to highly complex mechanisms by which the Central Nervous System store and organize experiences every day, developed along 4 billion years of evolution; thereby learning and memory are poorly understood bio-logical processes. The finding of the unsuspected intrinsic property of melanin to transforms light into chemical energy through water dissociation, as chlorophyll in plants; opens a new and wider horizon in the form in which the CNS generate and distribute chemical energy transporting it through molecular hydrogen produced by substantia nigra of mesencephalon and other pigmented structures. The mechanisms by which human modifies their behavior through learning and memory remain a mystery despite several decades of research. However, the unexpected role of melanin molecule bioenergetics of first order, very above the chlorophyll and glucose, indicates that the study of the fascinating processes involved in learning and memory several levels, needs to be started with the study of the generation and distribution of energy neuro-melanin -releasing to all the brain. Glucose is the universal precursor of any organic matter in our body, but cannot provide the energy that its own metabolism requires. In this article, we explain succinctly, the way hydrogen molecular (H2) -gas-, from the dissociation of water by the neuro melanin, moves from its source and permeates easily through the different structures of the Central Nervous System, as well as be the smaller atom, does not combine with water, moving through it in accordance with the laws of the simple diffusion. Molecular hydrogen is the main carrier of energy that nature uses in the entire universe, so that, once the neuro melanin separates it from the water, this displaces transporting its precious cargo of energy and its remarkable antioxidant capacity capable of reduce oxygen and form water.